2018
DOI: 10.1038/s41420-018-0078-x
|View full text |Cite|
|
Sign up to set email alerts
|

Cellular and molecular responses to acute cocaine treatment in neuronal-like N2a cells: potential mechanism for its resistance in cell death

Abstract: Cocaine is a highly abused drug that causes psychiatric and neurological problems. Its entry into neurons could alter cell-biochemistry and contribute in the manifestation of early pathological symptoms. We have previously shown the acute cocaine effects in rat C6 astroglia-like cells and found that these cells were highly sensitive to cocaine in terms of manifesting certain pathologies known to underlie psychological disorders. The present study was aimed to discern acute cocaine effects on the early onset of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 61 publications
2
14
0
Order By: Relevance
“…The cocaine concentration chosen by this study was 1 µg/mL, compared to previous literature relating to both cardiac and non-cardiac in vitro models this dosage lies within the plasma ranges conventionally observed in recreational drug users [ 12 , 19 , 20 , 21 , 22 , 23 , 24 ]. The cocaine treatment selected in the present study was also considered in relation to reports that have shown insufflation of 1.5 mg/kg (equating to 105 mg/70 kg person) results in peak urine concentrations of 0.3 µg/mL with post-mortem results highlighting mortality in 100 cases at cocaine concentrations of 9.8 1 µg/mL) and other studies demonstrating cocaine induced apoptosis between 0.1–1.0 µmol/mL treatments [ 25 , 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…The cocaine concentration chosen by this study was 1 µg/mL, compared to previous literature relating to both cardiac and non-cardiac in vitro models this dosage lies within the plasma ranges conventionally observed in recreational drug users [ 12 , 19 , 20 , 21 , 22 , 23 , 24 ]. The cocaine treatment selected in the present study was also considered in relation to reports that have shown insufflation of 1.5 mg/kg (equating to 105 mg/70 kg person) results in peak urine concentrations of 0.3 µg/mL with post-mortem results highlighting mortality in 100 cases at cocaine concentrations of 9.8 1 µg/mL) and other studies demonstrating cocaine induced apoptosis between 0.1–1.0 µmol/mL treatments [ 25 , 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Initially the effect of treatment with cocaine at concentrations ranging from 0.5 to 7 mM for 24 and 48 h on cell viability was assessed. The selection of cocaine concentrations was based on earlier reports ( 20 , 23 ), and the lag period and doubling time of these cells ( 17 ) were used as the criteria for treatment durations of 24 and 48 h. Compared with the corresponding controls, cocaine significantly decreased the cell viability at these time points ( Fig. 1A and B ; P<0.01 or P<0.001).…”
Section: Resultsmentioning
confidence: 90%
“…To investigate the effects of cocaine and alcohol on tubulin dynamics, we performed a MT-based assay (Cytoskeleton, Inc., Denver, CO, USA) [25][26][27] in SH-SY5Y neuroblastoma cells treated with 100 mM EtOH [10] and 1 mM cocaine [8] (n=6/group) for 3 days. This commercially available kit separates large complexes of polymerized MTs attached to nuclei and Golgi bodies into bound and non-polymerized free tubulins.…”
Section: Methodsmentioning
confidence: 99%
“…We performed cell binding assays in vitro in SH-SY5Y cells with [ 11 C]MPC-6827 following our previously published protocols. [28][29][30] The cells were treated with 100 mM EtOH or 1 mM cocaine [8] (n = 6/group) for 3 days. We then measured radiotracer binding by adding [ 11 C]MPC-6827 (1-2 µCi/well) and incubating the cells for 5, 30, 60, and 90 min at room temperature (n = 6/time point).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation